2022
DOI: 10.1093/bjsopen/zrac026
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile infection after ileostomy closure and anastomotic failure in rectal cancer surgery patients

Abstract: Background Diverting ileostomy during resection of rectal cancer is frequently performed in patients at risk of anastomotic failure. Clostridium difficile infection (CDI) is reported to be frequent in patients who receive ileostomy closure with a questionable association to postoperative anastomosis leak. The primary aim of this study was to determine the incidence of CDI following ileostomy closure in patients who underwent rectal cancer surgery; the secondary aim was to assess the rate of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Despite this, with the reversal of faecal diversion, the rapid change in the environment of the intestinal cavity may stimulate the breeding of some conditional pathogens, such as Clostridium difficile, which increases the risk of infection and anastomotic leakage. 75 Therefore, the use of local antibiotics before the reversal of faecal diversion may be necessary. 76 In addition to immature goblet cells, we also demonstrated defective differentiation of goblet cells caused by the absence of mechanical stimulation in the defunctioned intestine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, with the reversal of faecal diversion, the rapid change in the environment of the intestinal cavity may stimulate the breeding of some conditional pathogens, such as Clostridium difficile, which increases the risk of infection and anastomotic leakage. 75 Therefore, the use of local antibiotics before the reversal of faecal diversion may be necessary. 76 In addition to immature goblet cells, we also demonstrated defective differentiation of goblet cells caused by the absence of mechanical stimulation in the defunctioned intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our data showed that the antimicrobial peptides of the epithelium in the defunctioned intestine were significantly increased, compensating for the defective function of the intestinal barrier. Despite this, with the reversal of faecal diversion, the rapid change in the environment of the intestinal cavity may stimulate the breeding of some conditional pathogens, such as Clostridium difficile , which increases the risk of infection and anastomotic leakage 75 . Therefore, the use of local antibiotics before the reversal of faecal diversion may be necessary 76 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of a total of 1263 papers screened, 11 (10 retrospective cohort studies and 1 randomized controlled trial [5][6][7][8][9][10][11][12][13][14][15]) met the inclusion criteria and were analysed (Fig. 1), including a previous paper from our group [5].…”
Section: Study Population and Systematic Reviewmentioning
confidence: 99%
“…Colorectal surgery has been identified as a risk factor for Clostridium difficile infection (CDI) [1][2][3], although its occurrence is relatively rare, since as it has been reported in only 1.5% of patients [4]. However, stoma closure surgery has the highest incidence rate of CDI among abdominal procedures, ranging from 1.6 to 8.7% of cases [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%